First Detection of Circular Polarization in Radio Continuum Toward a Massive Protostar - A. G. Cheriyan; S. Vig; Nirupam Roy; Samir Mandal; C. Carrasco-González; A. Rodríguez-Kamenetzky; A. Pasetto (The Astrophysical Journal Letters)
Polarization measurements provide strong constraints on magnetic fields in star-forming systems. While magnetic field estimates of a few kG have been obtained near the surfaces of low-mass protostars, there are no analogous measurements in the immediate vicinity of the surface of massive protostars. We report the measurement of radio continuum circular polarization (CP) toward a massive protostar, IRAS 18162–2048, for the first time, using Karl G. Jansky Very Large Array observations. The fractional CP varies between 3% and 5% across the observed frequency range of 4–6 GHz. We consider multiple hypotheses for the production of CP and propose (i) gyrosynchrotron emission and (ii) Faraday conversion due to turbulence in the magnetic medium—both driven by mildly relativistic electrons as plausible mechanisms. We estimate, for the first time, a magnetic field B  ≳ 20–35 G close to the massive protostar. The Lorentz factor of the low-energy electrons is estimated to be in the range γ _min  ∼ 5–7 for gyrosynchrotron emission and 80–100 for Faraday conversion from our observations. The magnetic field estimate can provide important constraints to the formation models of massive stars.